2019
DOI: 10.1021/acs.cgd.9b00910
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism and Morphology Folklore

Abstract: Polymorphism of molecular crystals was Joel Bernstein’s (1941–2019) scientific focus. Polymorphism also has been the subject of lore: (1) McCrone made popular the belief that the longer you study a substance the more polymorphs you are likely to find, and (2) Bernstein made popular so-called disappearing polymorphs, forms that no matter how long you look you can no longer find (in the absence of extraordinary measures). Here, we add the following lore: (3) Molecular crystals with helicoidal morphologies are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…A large proportion (up to one-third) of molecular crystals can be made to twist as they grow. 38,[110][111][112][113] In some families of crystals, such as binary charge transfer complexes, the proportion can be greater than one-half. 114 This group includes many common materials that have been studied for decades or more.…”
Section: Ubiquitymentioning
confidence: 99%
“…A large proportion (up to one-third) of molecular crystals can be made to twist as they grow. 38,[110][111][112][113] In some families of crystals, such as binary charge transfer complexes, the proportion can be greater than one-half. 114 This group includes many common materials that have been studied for decades or more.…”
Section: Ubiquitymentioning
confidence: 99%
“…Several crystal twisting mechanisms have been reported in previous studies. The size dependence of twisting magnitude in crystals is identified as one of the characteristics of geometric frustration, a primary mechanism of twisting in molecular crystals. In the geometrical frustration mechanism, a molecular arrangement corresponding to the twisted crystal is physically preferred, even with elastic stress (strain) associated with the inevitable misfit due to steric hindrances at the molecular scale or small crystalline sizes. However, these twisted crystals cannot be realized globally, i.e., in large crystals, because the elastic energy associated with stress increases as twisted crystal size increases.…”
Section: Resultsmentioning
confidence: 99%
“…Besides lysozyme and thaumatin, growth-induced twisting has been reported in inorganic crystals, , organic crystals, , pharmaceutical crystals, , semiconductor crystals, and polymer spherulites. , As most of these studies were conducted using optical and electron microscopy, the observed magnitudes of twisting were significantly larger than those in protein crystals observed using digital X-ray topography. Thus, the evaluation of slight twisting via digital X-ray topography in different materials could lead to the discovery of more twisted crystals.…”
Section: Introductionmentioning
confidence: 99%
“…To introduce a paper in honor of the 2021 Wolf Prize winners who invented tailor-made additives (or auxiliaries) (TMAs) [1][2][3][4] for transformations of growing crystals, we reckoned correctly that there must be a Yiddish story about a tailor that could provide a point of departure. [5] Can wisdom from a tailor of folklore [6] inform our essay about crystal tailors?…”
Section: Tailorsmentioning
confidence: 99%